Potensi Selulosa Bakteri Sebagai Pembalut Luka Ideal dan Penghantar Obat (Drug Delivery) - Liau, Selva Susilowati; Hidayat, Muslikhin; Sulistyo, Hary (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The wound healing process requires an environment that can maintain moisture, absorb excess exudate, and is biodegradable. Conventional wound dressings such as cotton, gauze, and bandages cause wound dehydration. Bacterial cellulose derived from the fermentation of coconut water by Acetobacter xylinum bacteria has unique characteristics that have the potential to be an ideal wound dressing because it can provide a moist environment. It also has good mechanical properties, biodegradability, high biocompatibility, and is non-toxic. Bacterial cellulose produces fine fibres forming a thin layer of extracellular polysaccharides. Such fibre makes it possible to bind to the molecules of the drug. This research will study the mechanical properties and efficiency of drug mass transfer from bacterial cellulose membranes with different carbon sources, namely glucose and fructose, with fermentation time variations of 3, 5, and 7 days. The results showed that the characteristic value of the fructose carbon source was superior to that of glucose. The glucose carbon source has a membrane thickness of 0.81; 6,93; 10.61 mm; fructose is 2.80; 8,41; 13.40 mm. The highest absorption capacity, stress, elongation and drug mass efficiency value is obtained by a fructose carbon source with a fermentation time of 7 days, and for absorption capacity obtained at 1.1640 g/g, stress value 105.9 N with elongation 19.90 mm and drug mass efficiency 4.085%